Phrasal Discourse Style in Cross-Disciplinary Writing: A Comparison of Phrasal Complexity Features in the Results Sections of Research Articles - Parviz, Muhammed; Jalilifar, Alireza; Don, Alexanne (Círculo de Lingüística Aplicada a la Comunicación, 2020)
The present study aimed at exploring how research article writers from two academic disciplines exploit phrasal complexity features (PCFs) to verbalize the results sections of research articles with the eventual aim of assisting advanced EFL writers with their composition strategies. To this end, following a manual search, 200 empirical research articles in the fields of Applied Linguistics and Physics were comparatively examined. Due to the low rate of success of tagging programs in identifying the occurrences of PCFs, the datasets were also manually analyzed. The results revealed that the research article writers drew upon three high-frequency phrasal complexity features, namely, pre-modifying adjectives, post-modifying prepositional phrases, and nominalizations. The study also revealed that the results sections of research articles included different amounts of exceedingly complex patterns of pre-modification, a hybrid of novel appositive structures, and great reliance on hyphenated adjectives. Overall, we believe that these findings can be used to heighten the awareness of academic writers and instructors regarding the linguistic characteristics of academic writing and of the variations of how such phrasal features of compression are constructed in different academic subjects.